Hard Skill, Soft Skill dan Efikasi Diri Terhadap Kesiapan Kerja Mahasiswa Tingkat Akhir FEB Perguruan Tinggi di Kota Bandar Lampung - Nurbaiti; Almira Devita Putri (Universitas Sam Ratulangi, 2024)
This nation's graduates not only compete with their own country but also with foreign countries who can easily work in Indonesia so it is important for every individual who is ready to work in Indonesia to have good hard skills, soft skills, and self-efficacy. This research was conducted to find out the relationship between Hard Skills, Soft Skills, and Self-Efficacy and Work Readiness. The respondents of this research were FEB University students in Bandar Lampung with a sample of 97 people. To process the data, data analysis from this research used SPSS, the type of data taken was primary data taken directly by the researcher. Secondary data can be obtained from relevant sources such as books, scientific journals, and articles on the internet. This research concluded that there is a positive and significant influence between Hard Skills (X1) and Self-Efficacy (X3) on work readiness (Y). However, there is no significant influence between Soft Skills (X2) on Work Readiness (Y). Hard skills, soft skills, and self-efficacy together have a significant positive effect on the work readiness of FEB Final Year students in Higher Education in Bandar Lampung City.